A CONCEPTUAL FRAMEWORK SUPPLY CHAIN PERFORMANCE ALONG SEVERAL SOURCING OF RISK IN SMALL MEDIUM ENTERPRISE IN MALAYSIA - Jannah Munirah Binti Mohd Noor; Akmal Aini Othman; Shatina Saat; Azila Jaini (International Journal of Accounting, Finance and Business, 2021)
Theory, framework, tools, and techniques used to analyse Small and Medium Manufacturing Enterprise (SME) have often been designed for application in large Enterprise. This is predominantly the case when it comes to Supply Chain Management (SCM) and Supply Chain Risk Management (SCRM). SMEs, however, particularly in Malaysia, have unique characteristics and challenge. The Covid19 pandemic has forced supply chain management researcher and practitioners to question is, where does supplier chain management go from here? What has supply chain management learned from the COVID19 crisis can applied in future? Both in day-to-day operations and in preparation for the next global mega disasters? Are they can sustain in the marketplace after all this risk? If they can sustain what are the mitigation strategy and what is the resilience strategy significant for the Small Medium Enterprise. This paper presents an initial attempt to bridge this theoretical gap the development of a conceptual framework for the analysis of Supply Chain Risk Management in Small Medium Enterprise in Malaysia.